Change in the pattern of community economy in flood area : Case study Chee Wang Kan Village, Mancha Khiri District, Khon Kaen Province. - Putsyainunt, Bodee (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The objective of this article is to understand the general context of the Chee Wang Kanvillage, including the pattern of change in the community under the process of capitalism.This study employed the concept of community economy. In-depth interviews with 10 keyinformants and 103 household representatives were applied together with guided questions.The study found that the previous pattern of community economy in Chee Wang Kanvillage, since 1924, was agriculture, based on cropped rice for their own consumption andfish from the Chee River for their own consumption and for sale. Since 1989, the advanceof agriculture technologymeant that they started to use walking tractors on their farms. Thepattern of the community economy in Chee Wang Kan village changed to be agricultureproducts for sale. Prior to 2000, area suffered flooding that led more laborers in thecommunity to migrate to find work in Bangkok. Consequently, this changed the villagersâlivelihoods, which became a mixture of non-agriculture and agriculture products for sale.This situation continues to the present time. However, the pattern of community economyin Chee Wang Kan village has adapted to suit the context of the community, having notonly agriculture but also a non-agriculture pattern. This has ensured the maintenance of thecommunity economy pattern, under the influence of capitalism, to the present time.Keywords: Community economy, Pattern of community economy, Capitalism,Non-agriculture, Flood area